Eco-friendly dyeing of modified cotton fabrics with grape pomace colorant: Optimization using full factorial design approach - Noureddine Baaka; Wafa Haddar; Manel Ben Ticha; Mohamed Farouk Mhenni (Journal of Natural Fibers, 2019)
Grape pomace, which is a winery waste is studied and experimented to serve as a source of natural dyes that could be utilized in textile dyeing. In previous studies, it was found that grape pomace released from wine industry contains valuable resource of abundant natural coloring substances. The present work involves the optimization of dyeing process of cotton by natural colors extracted from grape pomace. The optimized dyeing conditions were; dyeing bath temperature 100°C, dyeing time 55 min, and dye bath pH 8. In addition, it was demonstrated that the dye bath of dyed cotton reduced the Chemical Oxygen Demand (COD) and the Biological Oxygen Demand (BOD)5 of the dye bath.